Gene set analysis of transcriptomics data identifies new biological processes associated with early markers of atherosclerosis but not with those of osteoporosis: Atherosclerosis-osteoporosis co/multimorbidity study in the Young Finns Study - Mishra Binisha H.; Sievänen Harri; Raitoharju Emma; Mononen Nina; Viikari Jorma; Juonala Markus; Laaksonen Marika; Hutri-Kähönen Nina; Kähönen Mika; Raitakari Olli T.; Lehtimäki Terho; Mishra Pashupati P. (Elsevier, 2022)
Aim
We aimed at identifying the shared biological processes underlying atherosclerosis-osteoporosis co/multimorbidity.
Methods
We performed gene set analysis (GSA) of whole-blood transcriptomic data to identify biological processes shared by the early markers of these two diseases. Early markers of diseases, carotid intima-media thickness (CIMT) for atherosclerosis and trabecular bone mineral density (BMD) from distal radius and tibia for osteoporosis, were used to categorize the study participants into cases and controls. Participants with high CIMT (>90th percentile) were defined as cases for subclinical atherosclerosis. Study population-based T-scores for BMD were calculated and T-score
−1 was used for the definition of low BMD cases i.e., early indicator of osteoporosis.
Results
We did not identify any gene sets jointly associated with early markers of atherosclerosis and osteoporosis. We identified three novel and replicated 234 gene sets significantly associated with high CIMT with false discovery rate (FDR) ≤ 0.01. Only two genes, both related to the immune system, were identified to be associated with high CIMT by traditional differential gene expression analysis. However, none of the studied gene sets or individual genes were significantly associated with tibial or radial BMD. The three novel CIMT associated gene sets contained genes involved in copper homeostasis, neural crest cell migration and nicotinate and nicotinamide metabolism. The 234 replicated gene sets in this study are related to the immune system, hypoxia and apoptosis, consistent with the existing literature on atherosclerosis.
Conclusions
This study identified novel biological processes associated with high CIMT but not with reduced BMD.